Practical purpose to work on spiritual competence in classroom: The drops of good desires (Journal of Parents and Teachers, 2012)
Working on the spiritual competence means to include its four levels, inclusive and non-exclusive ones: basic, transcendent, religious and confessional. It is an essential condition to leave from the own person and his/her closer experiences, in order to transcend little by little. We will go from the experiences in the basic competence, from the search for questions and answers in transcendent and religious competence, to go back again to the existential in the confessional competence. The suggested purpose is for 5-7 year old kids, so the funny, happy and closer character takes priority. It is based on what they think, feel and do.
Keywords: expriencies; Water; Competences; Spirituality; Life; Forgiveness; Love.